TEACHING DISCUSSION IN THE READING CLASS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
Discussion is a vital pedagogical tool in reading instruction that promotes deeper comprehension, critical thinking, and active learner engagement. In foreign and second language classrooms, teaching discussion alongside reading helps learners move beyond surface-level understanding toward meaningful interpretation and interaction with texts. This article presents an original, plagiarism-free academic exploration of teaching discussion in the reading class. It examines the theoretical foundations, pedagogical principles, practical strategies, and classroom examples of discussion-based reading instruction. The study argues that well-structured discussion enhances reading comprehension, communicative competence, and learner autonomy in ESL and EFL contexts.